Maturation of active zone assembly by Drosophila Bruchpilot. - Fouquet, W; Owald, D; Wichmann, C; Mertel, S; Depner, H; Dyba, M; Hallermann, S; Kittel, R; Eimer, S; Sigrist, S (2009)
Synaptic vesicles fuse at active zone (AZ) membranes where Ca(2+) channels are clustered and that are typically decorated by electron-dense projections. Recently, mutants of the Drosophila melanogaster ERC/CAST family protein Bruchpilot (BRP) were shown to lack dense projections (T-bars) and to suffer from Ca(2+) channel-clustering defects. In this study, we used high resolution light microscopy, electron microscopy, and intravital imaging to analyze the function of BRP in AZ assembly. Consistent with truncated BRP variants forming shortened T-bars, we identify BRP as a direct T-bar component at the AZ center with its N terminus closer to the AZ membrane than its C terminus. In contrast, Drosophila Liprin-alpha, another AZ-organizing protein, precedes BRP during the assembly of newly forming AZs by several hours and surrounds the AZ center in few discrete punctae. BRP seems responsible for effectively clustering Ca(2+) channels beneath the T-bar density late in a protracted AZ formation process, potentially through a direct molecular interaction with intracellular Ca(2+) channel domains.